2008
DOI: 10.1063/1.2805386
|View full text |Cite
|
Sign up to set email alerts
|

Probing the electronic and structural properties of doped aluminum clusters: MAl12− (M=Li, Cu, and Au)

Abstract: Photoelectron spectroscopy ͑PES͒ is combined with theoretical calculations to investigate the electronic and atomic structures of three doped aluminum clusters, MAl 12 − ͑M = Li, Cu, and Au͒. Well-resolved PES spectra have been obtained at two detachment photon energies, 266 nm ͑4.661 eV͒ and 193 nm ͑6.424 eV͒. Basin-hopping global optimization method in combination with density-functional theory calculations has been used for the structural searches. Good agreement between the measured PES spectra and theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 52 publications
4
37
0
1
Order By: Relevance
“…Previous ab initio calculations on smaller aluminum clusters doped with copper [74][75][76][77][78] do not fully agree on the preferred substitution site for the copper atom. Our results show that copper prefers to occupy interior positions in host aluminum clusters with 49-62 atoms, although the energetic cost for surface segregation of copper is not very large: The most stable homotop with copper at the cluster surface is roughly 0.2 eV above the correct ground state.…”
Section: Theoretical Resultsmentioning
confidence: 98%
“…Previous ab initio calculations on smaller aluminum clusters doped with copper [74][75][76][77][78] do not fully agree on the preferred substitution site for the copper atom. Our results show that copper prefers to occupy interior positions in host aluminum clusters with 49-62 atoms, although the energetic cost for surface segregation of copper is not very large: The most stable homotop with copper at the cluster surface is roughly 0.2 eV above the correct ground state.…”
Section: Theoretical Resultsmentioning
confidence: 98%
“…Most of the theoretical investigations are limited to doped aluminum clusters containing around 13 atoms as the neutral Al 13 might exhibit a symmetric icosahedral structure. While these studies predicted a caged structure with the TM atom occupying the central position for Al 11 TM (TM=Ni, Cu) [13,19], Al 12 TM (TM=Co, Ni, Cu) [13,14,19], Al 13 TM (TM= Cu, Au, Ni) [13,18,19], and Al 14 TM (TM=Cu) [19], as well as for anionic Al n Cu -(n=11-14) [19,21] and Al n Au -(n= 12) [21], minimum energy structures with the TM atom residing on the cluster surface were found for Al 12 TM (TM= Cr, Mn, Fe, Cu, Ag, Au) [14,18] and Al 13 Ag [18]. The different positions of the TM atom have been explained in terms of the ionization potential [19] and atomic radius [14,19] of the dopant atom.…”
Section: Discussionmentioning
confidence: 99%
“…Varying the dopant material and thus the atomic radius and the number of valence d electrons allows for changing the electronic and eventually also the geometric structure in a controlled manner. For instance, a combined experimental and theoretical study showed that Al 12 Cu -structurally resembles the icosahedral Al 13 -with the Cu atom occupying the central site while doping with gold yields a strongly distorted and opened structure caused by the large atomic radius of the Au atom [21].…”
Section: Introductionmentioning
confidence: 99%
“…The spherical jellium model predicts that clusters with 2, 8, 20, 40, … VEs have higher stability due to the closure of electronic shells. [1] A popular example is the magic I h Al 13 À cluster, which has 40 valence electrons, constituting a filled-shell configuration (1s) 2 (1p) 6 (1d) 10 (2s) 2 (1f) 6 (2p) 6 -A C H T U N G T R E N N U N G (1f) 8 . [2,3] Each electron shell is characterized by a radial quantum number N and an angular quantum number L. The valence electrons of the constituent atoms in simple pure metal clusters can be considered as itinerant.…”
mentioning
confidence: 99%